Critical Role of Myeloid-Derived Suppressor Cells in Tumor-Induced Liver Immune Suppression through Inhibition of NKT Cell Function - Zhang, Hongru; Li, Zheng; Wang, Li; Tian, Gaofei; Tian, Jun; Yang, Zishan; Cao, Guangchao; Zhou, Hong; Zhao, Liqing; Wu, Zhenzhou; Yin, Zhinan (Frontiers in Immunology, 2017)
Cancer cells induce an in-situ immune-suppressive microenvironment, which is critical for tumor escape, growth, and metastasis. Recent studies have reported immune suppression from remote tumors, suggesting a systemic immune tolerance upon tumor burden. But the underlying mechanism(s) were largely unknown. In this study, we found that remote tumor bearing mice performed dramatically attenuated pathogenesis of Concanavalin A (Con A) induced acute hepatitis, as indicated by decreased release of alanine aminotransferase (ALT), alleviated tissue necrosis and reduced production of pro-inflammatory cytokines. Intracellular cytokine staining results showed that interferon-γ (IFN-γ) production in NKT cells, not CD4+ T cells, was significantly decreased upon tumor burden, suggesting an important role of NKT cells. We also found remarkably increased myeloid-derived suppressor cells (MDSCs) in tumor bearing mice, and depletion/transfer experiments demonstrated that these cells were responsible for the ameliorated hepatitis through inhibiting IFN-γ production of NKT cells. Further researches revealed that the inhibitory effects of MDSCs were mediated via membrane-bounded transforming growth factor β (TGF-β) in a cell contact dependent manner. Moreover, we presented evidence that the recruitment of MDSCs into liver in tumor bearing mice was mediated by CXC chemokine receptor 2 (CXCR2), and tumor-derived TGF-β was critical in up-regulating CXCR2 ligands (CXCL1/2/5) in liver tissue. In summary, our results defined a novel mechanism of liver immune suppression triggered by growing remote tumor, and provided possible therapeutic targets against these MDSCs.